Business Models for Different Future Electricity Market Players - Khajeh, Hosna; Firoozi, Hooman; Laaksonen, Hannu; Shafie-khah, Miadreza (CRC Press, 2022)
This chapter firstly introduces the existing and newly emerged players participating in different markets and trading structures in a smart grid environment. These market players are prosumers, aggregators, virtual power plants (VPP), community managers, local market operators, and system operators including distribution system operators (DSO) as well as transmission system operators (TSO). Afterward, different business models and trading structures are introduced in the section. The business models and trading structures that are assessed in this chapter are local electricity markets, peer-to-peer (P2P) trading, aggregator-based trading model, and flexibility local markets. In local markets, prosumers are assumed to trade locally under the supervision of a local market operator. In P2P trading, prosumers are able to choose their trading partners and trade energy bilaterally. In an aggregator-based model, however, prosumers negotiate contracts with an aggregator to provide the power system with energy. In each model, market participants are specified and their roles and responsibilities are defined as well. Finally, the chapter introduces a new local market structure for trading flexibility services. It proposes a structure in which small-scale resources will be able to provide both local and system-wide flexibility and ancillary services. This business model is a driver unlocking the flexibility potential of small-scale prosumers and consumers so as to participate in increasing the reliability and security of the local and system-wide power networks.
Keywords: prosumers; local electricity markets; local flexibility markets; P2P electricity trading; aggregator-based electricity trading; future electricity markets; business models; fi=Sähkötekniikka|en=Electrical Engineering|